Microfluidic device to investigate factors affecting performance in biosensors designed for transdermal applications - Sanjiv Sharma (Lab Chip, 2012)
In this work we demonstrate a novel microfluidic based platform to investigate the performance of 3D out-of-plane microspike array based glucose and lactate biosensors. The microspike array was bonded with a glass slide and modified with glucose oxidase or lactate oxidase using covalent coupling chemistry. An epoxy-polyurethane based membrane was used to extend the linear working range (from 0 to 25mM of substrate) of these biosensors. Both lactate and glucose sensors performed well in the clinically relevant substrate concentration range. Glucose microspikes were further investigated with respect to the effects of substrate transfer by incorporation into a microfluidic system. Data from the microfluidic system revealed that the sensor response is mainly dependent on enzyme kinetics rather than membrane permeability to glucose. The robustness of the sensors was demonstrated by its consistency in performance extending over 48 h.